2012
DOI: 10.1128/aem.00085-12
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Aerobic Ripening Bacteria at the Cheese Surface Is Limited by the Availability of Iron

Abstract: ABSTRACTThe microflora on the surface of smear-ripened cheeses is composed of various species of bacteria and yeasts that contribute to the production of the desired organoleptic properties. The objective of the present study was to show that iron availability is a limiting factor in the growth of typical aerobic ripening bacteria in cheese. For that purpose, we investigated the effect of iron or siderophore addition in model cheeses that were coinoculated with a yeast and a ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 40 publications
1
49
1
Order By: Relevance
“…Although previous studies demonstrated that iron is limiting for Glutamicibacter, Brevibacterium, and Corynebacterium species growing on cheese (Monnet et al, 2012(Monnet et al, , 2010, the preponderance of siderophore and other iron acquisition genes we observed being horizontally transferred suggests that the same is true across bacterial phyla. Limiting iron is a deliberate strategy on the part of mammalian hosts to block the growth of infectious microbes, and this strategy influences the composition of milk because of the presence of lactoferrin (Ellison, 1994).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Although previous studies demonstrated that iron is limiting for Glutamicibacter, Brevibacterium, and Corynebacterium species growing on cheese (Monnet et al, 2012(Monnet et al, , 2010, the preponderance of siderophore and other iron acquisition genes we observed being horizontally transferred suggests that the same is true across bacterial phyla. Limiting iron is a deliberate strategy on the part of mammalian hosts to block the growth of infectious microbes, and this strategy influences the composition of milk because of the presence of lactoferrin (Ellison, 1994).…”
Section: Discussionmentioning
confidence: 57%
“…Five of the 10 largest HGT groups as measured by total number of genes (Groups 1, 2, 3, 7 and 8) contained siderophore transport systems (K02013-K02016). Low availability of iron in cheese is known to limit the growth of several bacterial species (Monnet et al, 2012(Monnet et al, , 2010. Previous work has also shown that genes involved in iron acquisition are present in higher numbers in cheese-associated species compared with closely related species from other environments (Monnet et al, 2010;Walter et al, 2014).…”
Section: Functions Encoded In Hgt Regionsmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar approach was applied for the study of the growth of L. lactis subsp. cremoris strains under conditions simulating cheddar cheese manufacture (Taïbi et al, 2011) and for the study of iron acquisition by Arthrobacter arilaitensis in experimental cheeses (Monnet et al, 2012 Experimental cheeses L. lactis subsp. lactis bcaT, codY, serA, cysK, gltD, lacC, gapA, gapB, pdhB, aldB, butA, noxE, murF, dnaK, chiA, pepN, gyrB, pi139, pi302 Experimental cheeses (Cretenet et al, 2011) L. lactis subsp.…”
Section: Real-time Pcr Methodsmentioning
confidence: 99%
“…For example, it is interesting to supplement genomic data, which give indications of the potential of a given microorganism in terms of metabolic activities, with gene expression data, which reveal the true capabilities of the microorganism inside the food product. Gene expression analyses have been performed with experimental cheeses or experimental fermented milks (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). To our knowledge, no study devoted to the quantification of gene transcripts in retail cheeses has been published as of this time.…”
mentioning
confidence: 99%